Integration of competency needs and continuity of care learning for midwifery students based on mobile applications in Indonesia: A mixed-methods study - Ari Indra Susanti; Ariyati Mandiri; Anis Novitasari; Harridhil Silmi; Didah; Qorinah Estiningtyas Sakilah Adnani; Lisa McKenna (Belitung Nursing Journal, 2026)
Background: Strengthening the quality of midwifery education is crucial to equip future midwives with the competencies required for contemporary practice. Continuity of Care (CoC) learning requires structured learning strategies, appropriate media, and effective evaluation mechanisms based on students’ needs. In this context, mobile applications can support CoC learning through flexible documentation and reporting systems. Objective: This study aimed to identify learning and competency needs for technology-enhanced CoC education among midwifery students. Methods: A convergent mixed-methods design was employed with midwifery students in the Bandung Metropolitan Raya region, West Java, Indonesia, in 2024. Purposive sampling was used to select 310 students for quantitative analysis using STATA 16.0. Qualitative data from online focus group discussions (FGDs) with 34 students were analyzed using NVivo 1.6.1. Results: Quantitative analysis identified learning strategy as the strongest predictor of CoC competency (r = 0.790, p < 0.001). Qualitative findings revealed two main themes: CoC Competencies (with subthemes of CoC Competency Objectives and CoC Core Competencies) and integrated CoC learning components (learning strategy, learning media, and learning evaluation). Conclusion: This study identified four essential components of mobile-based CoC learning, with learning strategies emerging as the strongest predictor of competency. These findings indicate that, although mobile technology enables efficient recording and reporting, it must be integrated with structured learning strategies to effectively strengthen midwifery competencies.